2019
DOI: 10.1016/j.celrep.2019.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Atoh1 Directs Regeneration and Functional Recovery of the Mature Mouse Vestibular System

Abstract: SUMMARY Utricular hair cells (HCs) are mechanoreceptors required for vestibular function. After damage, regeneration of mammalian utricular HCs is limited and regenerated HCs appear immature. Thus, loss of vestibular function is presumed irreversible. Here, we found partial HC replacement and functional recovery in the mature mouse utricle, both enhanced by overexpressing the transcription factor Atoh1. Following damage, long-term fate mapping revealed that support cells non-mitotically and modestly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 59 publications
4
79
0
Order By: Relevance
“…Furthermore, it is required for generating the majority of glia in the antenna (Jhaveri et al 2000;Sen et al 2005). As the first known transcriptional factors expressed in inner ear hair cells, Atoh1 is required for fate determination of those cells, and misexpression of Atoh1 in other cells such as the glial-like support cells is sufficient to generate hair cells (Bermingham et al 1999;Ben-Arie et al 2000;Zheng and Gao 2000;Kawamoto et al 2003;Izumikawa et al 2005;Srivastava et al 2013;Sayyid et al 2019). In the cerebellum, Atoh1 is required for cerebellar granule neuron formation in addition to other neurons types in the parabrachial, lateral lemniscal, and deep cerebellar nuclei, while not found to be important for gliogenesis (Ben-Arie et al 1997;Wang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is required for generating the majority of glia in the antenna (Jhaveri et al 2000;Sen et al 2005). As the first known transcriptional factors expressed in inner ear hair cells, Atoh1 is required for fate determination of those cells, and misexpression of Atoh1 in other cells such as the glial-like support cells is sufficient to generate hair cells (Bermingham et al 1999;Ben-Arie et al 2000;Zheng and Gao 2000;Kawamoto et al 2003;Izumikawa et al 2005;Srivastava et al 2013;Sayyid et al 2019). In the cerebellum, Atoh1 is required for cerebellar granule neuron formation in addition to other neurons types in the parabrachial, lateral lemniscal, and deep cerebellar nuclei, while not found to be important for gliogenesis (Ben-Arie et al 1997;Wang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…lin-32 was previously reported to regulate the neuronal fate specification of multiple cell lineages including neurons in the male tail (Portman and Emmons 2000;Zhao and Emmons 1995;Rojo Romanos et al 2017); CEPD, ADE and PDE dopaminergic neurons (Doitsidou et al 2008) and the URX oxygen-sensing neurons (Rojo Romanos et al 2017). Its mammalian homolog Atoh1 has also been implicated in the generation of inner ear hair cells (Bermingham et al 1999) and cerebellar granule neurons (Ben-Arie et al 1997), where overexpression can induce transdifferentiation of glial-like support cells into functioning hair cells in the cochlea and specify differentiation of mature cerebellar granule neurons at the expense of glial production in embryoid bodies (Izumikawa et al 2005;Srivastava et al 2013;Sayyid et al 2019). Furthermore, Atoh1 exhibits functional conservation with Drosophila atonal where it also promotes a neuronal fate (Ben-Arie et al 2000), while sensory precursors of the ato lineage generate the bulk of glia in the antenna (Jhaveri et al 2000;Sen et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it needs to be emphasized that our study was conducted in vitro and was limited to immature, early postnatal stages. While recent studies showed promise in regenerating vestibular hair cells in adult mice (9,82), the regeneration of cochlear hair cells in adult mice has proven thus far an impossible task (65) and reviewed in (83).…”
Section: Discussionmentioning
confidence: 99%
“…8; Sayyid et al, 2019, figure 2). The results of this study (Sayyid et al, 2019) show the importance of atoh1 gene expression in the hair cell regeneration response within the vestibular system.…”
Section: Future Directions For Applications Of Gene and Stem Cell Thementioning
confidence: 99%